Frameworks Enabling Ubiquitous Mixed Reality Applications Across Dynamically Adaptable Device Configurations - Weber, Sandro; Rudolph, Linda; Liedtke, Sven; Eichhorn, Christian; Dyrda, Daniel; Plecher, David A.; Klinker, Gudrun (Frontiers in Virtual Reality, 2022)
If Mixed Reality applications are supposed to become truly ubiquitous, they face the challenge of an ever evolving set of hard- and software systems - each with its own standards and APIs - that need to work together and become part of the same shared environment (the application). A unified standard is unlikely so we can not rely on a single software development stack to incorporate all necessary parts. Instead we need frameworks that are modular and flexible enough to be adapted to the needs of the application at hand and are able to incorporate a wide range of setups for devices, services, etc. We identified a set of common questions that can be used to characterize and analyze Mixed Reality applications and use these same questions to identify challenges as well as present solutions in the form of three frameworks tackling the fields of tracking & inference (UbiTrack), interaction (Ubi-Interact) and visualization (UbiVis). Tracking & inference has been tackled for quite some time now while interaction is a current topic with existing solutions. Visualization will be focused more in the future. We present several applications in development together with their future vision and explain how the frameworks help realize these and other potential apps.